2018
DOI: 10.1177/2150135117743211
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Acute Kidney Injury in Children Undergoing Cardiac Surgery: A Narrative Review

Abstract: Children undergoing cardiac surgery are at risk of developing acute kidney injury (AKI). Preventing cardiac surgery-associated AKI (CS-AKI) is important as it is associated with increased early- and long-term mortality and morbidity. Targeting modifiable risk factors (eg, avoiding poor renal perfusion, nephrotoxic drugs, and fluid overload) reduces the risk of CS-AKI. There is currently no strong evidence for the routine use of pharmacological approaches (eg, aminophylline, dexmedetomidine, fenoldopam, and ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 133 publications
0
11
0
Order By: Relevance
“…The pathophysiology of AKI is variable and includes hemodynamic compromise during surgery, hypovolemia, ischemic‐reperfusion injury, and cardiopulmonary bypass (CPB)‐induced inflammatory responses. In addition, age (patients who are < 12 months old), surgical complexity, CPB duration, preoperative hypoalbuminemia, and pulmonary hypertension are also risk factors that are associated with the development of AKI 3,4 . Several studies have suggested that reducing blood transfusion, avoiding nephrotoxic agents, reducing CPB duration, and using crystalloid fluids (rather than colloid fluids) may reduce AKI during cardiac surgery 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of AKI is variable and includes hemodynamic compromise during surgery, hypovolemia, ischemic‐reperfusion injury, and cardiopulmonary bypass (CPB)‐induced inflammatory responses. In addition, age (patients who are < 12 months old), surgical complexity, CPB duration, preoperative hypoalbuminemia, and pulmonary hypertension are also risk factors that are associated with the development of AKI 3,4 . Several studies have suggested that reducing blood transfusion, avoiding nephrotoxic agents, reducing CPB duration, and using crystalloid fluids (rather than colloid fluids) may reduce AKI during cardiac surgery 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of proximal tubular injury appears within 2 hours of cardiac surgery in both animal models and human biomarker studies 1114 , followed by evolution to clinical acute kidney dysfunction over a period of hours to days 15 . Incidence of AKI following pediatric cardiac surgery ranges from 25–64% depending on the specific population studied and definition used 11,1618 , with an associated mortality between 5–12% 19,20 . Development of AKI is also associated with increased duration of mechanical ventilation and length of hospital stay and may increase risk for development of chronic kidney disease 6,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…I welcome further dialog and even more well-designed comparative studies that prove the value of kSO2. Things that may reduce/improve AKI risk after cardiac operations Cytochrome-eicosanoid inhibition and AKI 4 High estimated pulmonary artery systolic pressure to predict acute kidney injury 5 Enteral flavone glycoside reduces cardiac surgery-Associated AKI in rats 6 N-acetyl cysteine to prevent postoperative AKI in preexistingrenal-failure 7 Naturetic peptide is best drug with evidence for prevention of AKI 7 Low-dose doxycycline in rats is protective against AKI 8 Early peritoneal dialysis to prevent AKI in neonates 9 Things that do not work for AKI prevention…”
Section: Acute Kidey Injury Risks During Cardiac Operations Are Too Nmentioning
confidence: 99%